Digital skills and sociodemographic variables in university teachers in the Peruvian Amazon during the COVID-19 pandemic. - Farfán Latorre, Marilú; Estrada Araoz, Edwin G.; Lavilla Condori, Willian Gerardo; Meza Orue, Llen A.; Yancachajlla Quispe, Luis I.; Rengifo Ramírez, Sheyla S. (Archivos Venezolanos de Farmacología y Terapéutica, 2022)
The objective of this research was to analyze the sociodemographic variables associated with the digital skills of university teachers in the Peruvian Amazon during the COVID-19 pandemic. The approach was quantitative, the design was non-experimental and the type was cross-sectional comparative descriptive. The sample consisted of 167 teachers from 3 universities to whom the Digital Teaching Competence Questionnaire was applied, an instrument with adequate metric properties (validity based on content and reliability). According to the results, the digital skills of 55.7% of university teachers are developed, 40.7% are partially developed and 3.6% are poorly developed. Similarly, it was determined that some sociodemographic variables such as age group and area of knowledge were significantly associated with the level of development of digital skills (p<0.05). It was concluded that university teachers were characterized by having digital skills developed in the post-pandemic context, which were more favorable in younger teachers and whose area of knowledge was Engineering and Architecture.